HEMOLYSIS OF RABBIT ERYTHROCYTES BY PURIFIED STAPHYLOCOCCAL ALPHA-TOXIN I. : Kinetics of the Lytic Reaction - Cooper, Louis Z. (1964)
Cooper, Louis Z. (New England Center Hospital, Boston, Mass.), Morton A. Madoff, and Louis Weinstein. Hemolysis of rabbit erythrocytes by purified staphylococcal alpha-toxin: I. Kinetics of the lytic reaction. J. Bacteriol. 87:127–135. 1964.—The hemolytic activity of purified staphylococcal alpha-lysin was found to be directly proportional to toxin concentration and inversely related to the log concentration of rabbit erythrocytes. Activity was directly proportional to the duration of lysin-red cell incubation until inactivating effects of heat and dilution became significant; this linear relationship was prolonged by incubation at a lower temperature and addition of bovine serum albumin. Study of the time course of hemolysis at different alpha-lysin concentrations revealed a family of sigmoid curves characterized by a prelytic lag phase and a period of rapid linear release of hemoglobin. The duration of prelytic lag varied inversely with the quantity of toxin, but the rate of hemolysis was directly proportional to toxin and red-cell concentrations. The presence of bovine serum albumin decreased the prelytic lag, prolonged the linear phase of the reaction, and increased total hemolysis. In the range of 25 to 46 C, the prelytic lag period became shorter with increase in temperature; at 48 to 52 C, it was markedly prolonged and hemolysis was strikingly diminished. As the incubation temperature was increased from 25 to 52 C, there was a decrease in the degree of maximal hemolysis, presumably due to thermal inactivation of alphalysin. The rate of hemolysis, when measured to 50% hemolysis, was optimal between 34 and 42 C but, when determined to the 10% level, was greatest between 40 and 46 C. The features of the hemolytic reaction suggest that staphylococcal alpha-toxin has the characteristics of an enzyme.